Early coronary stent thrombosis after bare metal stent implantation - Dubey, Laxman; Guruprasad, S; Subramanyan, G (Journal of College of Medical Sciences-Nepal, 2014)
Percutaneous coronary intervention with stenting has become the most widely performed procedure for the treatment of obstructive coronary artery disease. But, a major drawback of coronary stenting is the occurrence of stent thrombosis. Though rare, stent thrombosis can lead to ST segment elevation myocardial infarction or even sudden cardiac death. This is a case of early coronary stent thrombosis in a 58-year-old male patient, who presented with acute chest pain, Mobitz type II 2:1atrioventricular block and cardiogenic shock 15 days after percutaneous coronary intervention with bare metal stenting to the right coronary artery. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-2, 60-64 DOI: http://dx.doi.org/10.3126/jcmsn.v9i2.9690